Advances in bariatric surgery techniques in Brazil: An integrative review (Research, Society and Development, 2023)
Bariatric surgery is considered an option for patients with severe obesity who have not had significant success with non-surgical weight loss methods. However, although there are several techniques, little is discussed about them. In this context, the objective of this work was to explore new surgical techniques customized for patients indicated for bariatric surgery, also considering robotics as a support for these techniques. This is an integrative review of the last 10 years (2013 to 2023) using three bibliographic databases. 21 articles were used to compose the review. Among the existing techniques of bariatric surgery, the mini Gastric By-pass, the Duodenal Switch and the Single-Anastomosis Duodenal Switch (SADS) stand out. It can also be concluded that robotics has helped bariatric surgeries by offering greater solutions, improved three-dimensional visualization and more delicate movements, contributing to less invasive procedures and faster recoveries.